Prospect Study of Anti-inflammatory Activity by Identification of Muntingia calabura Leaf Infusion - Permana, Shenny S.S; Yusuf, Muchamad R.A; Putri, Aufa A.D; Sukmayani, Jasmine Y.; Sudrajat, Ratu Z.A.P; Khairinisa, Miski A.; Wahyuni, Indah S.; Rohmawaty, Enny; Bashari, Muhammad H.; Lesmana, Ronny; Rosdianto, Aziiz M. (Pharmacology and Clinical Pharmacy Research, 2024)
Many diseases occur due to inflammation that is not handled properly. One of the feature of inflammation is swelling or edema. Inflammation can be handled with traditional medicine, such as Muntingia calabura L. (M. calabura L.) Pharmacologically, this plant extract is reported to have antipyretic, analgesic, anti-inflammatory, antioxidant, and antibacterial. Metabolite compound contained in M. calabura L. has the potential as an anti-inflammatory agent. The objective of this study is to ascertain the secondary metabolites contained in M. calabura L. leaves infusion. This experimental research method includes the simplicia making and infusion of M. calabura L. leaves by cold infusion and phytochemical screening. This study also showed that the infusion of M. calabura L. leaves contained flavonoids, alkaloids, and triterpenoids. Overall, the findings indicate potential as an anti-inflammatory agent that requires further investigation, specifically in preclinical testing.